Translation of interviews from a source language to a target language: examining issues in cross‐cultural health care research. Issue 9 (2nd September 2014) - Al‐Amer, Rasmieh; Ramjan, Lucie; Glew, Paul; Darwish, Maram; Salamonson, Yenna
Abstract : Aims and objectives: To illuminate translation practice in cross‐language interview in health care research and its impact on the construction of the data. Background: Globalisation and changing patterns of migration have created changes to the world's demography; this has presented challenges for overarching social domains, specifically, in the health sector. Providing ethno‐cultural health services is a timely and central facet in an ever‐increasingly diverse world. Nursing and other health sectors employ cross‐language research to provide knowledge and understanding of the needs of minority groups, which underpins cultural‐sensitive care services. However, when cultural and linguistic differences exist, they pose unique complexities for cross‐cultural health care research; particularly in qualitative research where narrative data are central for communication as most participants prefer to tell their story in their native language. Consequently, translation is often unavoidable in order to make a respondent's narrative vivid and comprehensible, yet, there is no consensus about how researchers should address this vital issue. Design: An integrative literature review. Methods: PubMed and CINAHL databases were searched for relevant studies published before January 2014, and hand searched reference lists of studies were selected. Results: This review of cross‐language health care studies highlighted three major themes, which identify factors often reported to affect the translation and production of data in cross‐language research: (1) translation style; (2) translators; and (3) trustworthiness of the data. Conclusion: A plan detailing the translation process and analysis of health care data must be determined from the study outset to ensure credibility is maintained. A transparent and systematic approach in reporting the translation process not only enhances the integrity of the findings but also provides overall rigour and auditability. Relevance to clinical practice: It is important that minority groups have a voice in health care research which, if accurately translated, will enable nurses to improve culturally relevant care.